Use of EcoTILLING to identify natural allelic variants of rice candidate genes involved in salinity tolerance - Negrão, S.; Almadanim, C.; Pires, I.; McNally, K.L.; Oliveira, M.M. (Cambridge University Press, 2011)
Rice is a salt-sensitive species with enormous genetic variation for salt tolerance hidden in its germplasm pool. The EcoTILLING technique allows us to assign haplotypes, thus reducing the number of accessions to be sequenced, becoming a cost-effective, time-saving and high-throughput method, ideal to be used in laboratories with limited financial resources. Aiming to find alleles associated with salinity tolerance, we are currently using the EcoTILLING technique to detect single nucleotide polymorphisms (SNPs) and small indels across 375 germplasm accessions representing the diversity available in domesticated rice. We are targeting several genes known to be involved in salt stress signal transduction (OsCPK17) or tolerance mechanisms (SalT). So far, we found a total of 15 and 23 representative SNPs or indels in OsCPK17 and SalT, respectively. These natural allelic variants are mostly located in 3′-untranslated region, thus opening a new path for studying their potential contribution to the regulation of gene expression and possible role in salt tolerance.